The Angiotensin-Converting Enzyme Inhibitory State Promotes the Transformation of Non-Small Cell Lung Cancer Blood Supply Pattern Toward Vasculogenic Mimicry Formation - Xu, Kandi; Han, Huize; Luo, Yexin; Ye, Hong; Lin, Hongxia; Ni, Lei (Frontiers in Oncology, 2021)
Tumor microenvironment plays an important role in tumor proliferation, metastasis and angiogenesis. Local RAS is a key factor to tumor proliferation and metastasis in NSCLC microenvironment, but its role on angiogenesis and VM formation remains unclear. Although overwhelming majority of previous studies suggested that VM is well established in aggressive tumor and facilitates tumor growth and metastasis, we put forward different views from another angle. We proved that, status of tumor blood supply patterns, including VM channels and endothelial vessels, can dynamically exchange with each other along with local RAS fluctuations in microenvironment. Quantitatively, ACE2/ACEI promotes VM formation via Nodal/Notch4 activation; while structurally, ACE2/ACEI leads to a strong and solid structure of VM via inhibition of VE-cadherin internalization. These changes induced by ACE2/ACEI relates to relatively low metastasis rate and comforting prognoses of NSCLC patients.